2013
DOI: 10.1530/endoabs.32.p701
|View full text |Cite
|
Sign up to set email alerts
|

Obestatin is associated to muscle strength, functional capacity and cognitive status in old women

Abstract: Obestatin has been proposed to have anorexigenic and anti-ghrelin actions. The objective was to study obestatin concentrations in relation to handgrip strength, functional capacity and cognitive state in old women. The prospective study included 110 women (age, 76.93±6.32) from the Mataró Ageing Study. Individuals were characterized by anthropometric variables, grip strength, Barthel and assessment of cognitive impairment [Mini Cognoscitive Examination (MCE) Spanish version], depressive status by the Geriatric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
1
0
0
Order By: Relevance
“…In addition, it is involved in different physiological functions such as myocardial functional improvement in response to risk factors, participation in cardiovascular regulations by ghrelin, improved cardiac function, suppression of apoptosis of myocardial cell and protection of cardiac cell from cardiac damage. 25,43 According to the studies, our study confirmed the neuroprotective effects of OB, which has shown that it could reduce the neurotoxic effects of METH.…”
Section: Discussionsupporting
confidence: 74%
“…In addition, it is involved in different physiological functions such as myocardial functional improvement in response to risk factors, participation in cardiovascular regulations by ghrelin, improved cardiac function, suppression of apoptosis of myocardial cell and protection of cardiac cell from cardiac damage. 25,43 According to the studies, our study confirmed the neuroprotective effects of OB, which has shown that it could reduce the neurotoxic effects of METH.…”
Section: Discussionsupporting
confidence: 74%